Peran Guru dalam Evaluasi Pembelajaran di Kelas - Yadi Sutikno (Jurnal Maitreyawira, 2023)
Based on observations, there has not been much research on the role of teachers in evaluating learning in the classroom. Whereas the research mentioned above must be done to reveal information related to the teacher's role in evaluating learning in the classroom. Based on these observations, research will be conducted on the teacher's role in evaluating learning in the classroom. This study uses a qualitative method with the type of literature study. The teacher's role in improving the quality of learning is to provide value to students, to determine the level of success of students in the learning process, to determine the success of the learning objectives made by the teacher, to determine time efficiency in the learning process, and to determine the benefits of the learning objectives that have been set. implemented in the learning process.